Evaluation of Nutrient and Digestibility of Agricultural Waste Total Mixed Ration Silage as Ruminant Feed - Arsyadi Ali; Anwar Efendi Harahap; Jepri Juliantoni (Buletin Peternakan, 2023)
Difficulties in feeding ruminants, which generally use field grass, can be modified by utilizing forage waste from corn, rice and cassava using the total mixed ration (TMR) silage model to obtain feed that is rich in nutrients and long lasting. The study aimed of the study was to determine the nutritional value and digestibility of TMR silage using forage and concentrate waste from corn, rice and cassava. The research design used a completely randomized design with 3 treatments of agricultural waste and 6 replications. The treatment is CWS (corn waste silage); RWS (rice waste silage) and CVWS (cassava waste silage). The parameters tested were crude protein, crude fiber, crude fat, NDF, ADF, WSC, RFV, NH3, rumen PH, VFA, In vitro dry matter digestibility (IVDMD) and In vitro organic matter digestibility (IVOMD). The results showed that CVWS (cassava waste silage) increased crude protein, RFV and reduced NDF, while CWS (corn waste silage) reduced crude fiber and ADF, increased NH3 production, VFA and in vitro digestibility